Changes of electrocardiograms of animals with epinephrine heart damage in influences of stress and castration - Druziuk, R.; Denefil, O. (Journal of Education, Health and Sport, 2023)
The study of changes in electrocardiograms under the influence of stress on the body is relevant. The catecholamines released in this case cause disorders of the work of the heart and contribute to the development of cardiovascular pathology. Stress also causes suppression of testosterone synthesis and spermatogenesis. The aim of the study was - to analyze changes in electrocardiogram indicators in rats that have undergone castration and stress during the development of epinephrine heart damage (EHD). Material and methods of investigation. The study was performed on 240 white Wistar male rats, which were kept in one room on a standard diet and a vivarium regime. All animals were divided into four series: 1 – control, 2 – stress, 3 – castration, 4 – castration and stress. To simulated EHD, rats were injected once intramuscularly with a 0.18% solution of adrenaline hydrotartrate at the rate of 0.5 mg/kg of rat’s weight. Such a dose of adrenaline causes reliable regulatory changes in the functioning of the cardiovascular system under any environmental conditions already 1 hour after injection of the drug, without causing lethality among animals. Stress was induced in rats from 1.5 to 3 months of age. The animals were constantly kept in cages with the limitation of living space by two times for 1.5 months. Experimental modeling of the decrease in the level of sex hormones in rats was carried out using castration under sodium thiopental anesthesia (40 mg/kg). Autopsy of the anterior abdominal wall was made according to Ya.D. Kirshenblatt method. At the time of the beginning of EHD simulation, all animals were 4 months old. Electrocardiography (ECG) was made after 1, 3, 7, 14 and 28 days after injection of epinephrine hydrotartrate in volumes corresponding to body weight. ECG was made under thiopental-sodium anesthesia. For analysis, we took the durations of the PQ and QT intervals, the status of the ST segment from the isoline, and the amplitude of the T wave. The significance of the obtained differences between the results (minimum level of significance p<0.05) was assessed using the Kruskal–Wallis and Newman–Keuls tests (BioStat program, AnalystSoft Inc.). Results. When analyzing electrocardiogram indicators in the control groups of all four series, the following was noted. Analyzing T wave data, only a significantly greater amplitude of the T wave was noted in the 4th series of rats, compared to the 3rd, by 64.8% (p<0.001). In 1 series of animals, during the development of EHD after 3 days, significantly higher values of the duration of the PQ interval were noted, compared to the control by 28.0% (p<0.01), and compared to the previous period of the study by 34.3% (p<0.01). Also, at this time, the amplitude of the T wave, compared to the previous period of the study, was 2.3 times higher (p<0.001). In the 2nd series of animals, the amplitude of the T wave 7 days after the start of adrenaline injection was 84.3% greater (p<0.001) compared to the control. Also, after 28 days, compared to the previous period of the study, the amplitude of the T wave was smaller by 49.3% (p<0.01). When comparing the indicators with 1 series of rats, the following was noted. After 3 days, the duration of the PQ interval was shorter by 24.7% (p<0.01). The duration of the QT interval was not significantly different between animal series. Deviation of the ST segment from the isoline after 1 day of EHD was 76.2% (p<0.001) greater in 2 series of rats. The amplitude of the T wave in the 2nd series of rats, compared to the 1st, was 2.4 times greater after 3 days (p<0.001), after 7 days by 58.3% (p<0.001), and after 28 days it was smaller by 37.6% (p <0.01). In the 3rd series of animals, no significant changes in indicators were noted during the experiment, compared to the control series. When the indicators of 3 series of rats were compared with ones of 1 series, it was noted that after 3 days the duration of the PQ interval was shorter by 34.3% (p<0.01). When comparing the indicators of the 3rd series with the 2nd series of animals, the following was noted. 1 day after the injection of adrenaline, the deviation of the ST segment from the isoline was greater in animals that experienced long-term stress by 75.7% (p<0.001), and the T wave amplitude by 43.8% (p<0.001). 7 days after the injection of adrenaline, the amplitude of the T wave was greater in animals that experienced long-term stress by 34.1% (p<0.001). 14 days after the injection of adrenaline, the deviation of the ST segment from the isoline was greater in animals that experienced long-term stress by 96.7% (p<0.001), and the amplitude of the T wave by 45.8% (p<0.001). In the 4 series of animals, no significant changes in indicators were noted during the experiment, compared to the control series. Comparing the indicators of 4 series of rats with 1 series, it was noted that 1 day after the injection of adrenaline, the amplitude of the T wave was 2.5 times higher in 4 series of rats (p<0.001); after 3 days, the duration of the PQ interval was shorter by 24.7% (p<0.01). When comparing the indicators of the 4th series with the 2nd series of animals, the following was noted. 1 day after the injection of adrenaline, the deviation of the ST segment from the isoline was greater in animals that subjected to long-term stress by 64.9% (p<0.001), and after 3 days – by 69.5% (p<0.001). 7 days after the injection of adrenaline, the amplitude of the T wave was greater in animals that subjected to long-term stress by 43.8% (p<0.001). 28 days after the injection of adrenaline, the duration of the QT interval was longer in animals that underwent castration and stress by 17.8% (p<0.05). When comparing the indicators of 4 and 3 series of rats, it was noted that 1 day after the injection of adrenaline, the amplitude of the T wave was higher in 4 series of rats by 85.0% (p<0.001). Conclusions. The difference in the most vulnerable periods of damage to the myocardium by adrenaline was revealed in the studied groups of rats. For animals that are in normal conditions - after 3 days; for animals that lead a sedentary lifestyle - up to 7 days. Animals that underwent castration and animals that underwent castration and stress did not undergo reliable changes in the studied indicators of electrocardiograms.